KARAKTERISTIK SIFAT FISIKA KIMIA MEMBRAN DARI BERBAGAI FORMULA KOMPON - Nasruddin, Nasruddin (Balai Riset dan Standardisasi Industri Palembang, 2010)
The research aims to study the chracteristics of physical and chemical properties of membrane for pressing seeds to product palm kernel oil. The main material used for this study was natural rbber , synthetic rubber ,nitrile butandiene rubber( NBR),chloroprene rubber(CR),vucaniztion materials ,materials activist , abrasion rest and filler materials. The membrane consist of five vulcanization dormula through a process using an open mill.Membrane was tested in the laboratory by ASTM test method that includes: mooney visvometer ,hardness,tensile strength ,moludus of 200%,elongation at break,tear strength density and abrasion.Results of laboratory tests showed the treatment of compound D to get the best value , namely: hardness with the value 79 shore A; tensile strength 152kg/cm2;modulus 200% with the value of 40 kg/cm2, elongation at break with a 610%,tear streangth with value of 96kg/cm2;density with value of 1451 g/cm3 and abrasion rest itha value of 270,9mm3.